2005
DOI: 10.1007/s10789-005-0271-1
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Properties of PbI2 Doped with Fe and Ni

Abstract: A procedure is described for doping PbI 2 single crystals with Fe and Ni during vapor-phase growth in a closed system in the presence of excess iodine. The rate of mass transport in the system and the doping level of the crystals are shown to be governed by the dopant content in the source material and the source temperature. The effect of Fe and Ni doping on the low-temperature (5 K) exciton photoluminescence spectrum of PbI 2 is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
(3 reference statements)
1
7
0
Order By: Relevance
“…As established in the work [13], the increase in Fe concentration from 0.001 to 0.01 at. % is accompanied by a nonlinear increase in the exciton bandwidth and a decrease in the maximal amplitude.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…As established in the work [13], the increase in Fe concentration from 0.001 to 0.01 at. % is accompanied by a nonlinear increase in the exciton bandwidth and a decrease in the maximal amplitude.…”
Section: Resultssupporting
confidence: 64%
“…Nonetheless, there are a few studies reported on Fe-doped PbI 2 single crystals. They refer to the crystals grown from a vapour phase or by a Bridgman-Stockbarger method [13][14][15], as well as to Pb 1-x Fe x I 2 nanoparticles dispersed in polymer matrices [14]. The authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimony (Sb 3+ ) was found to introduce two deep traps situated at 0.21 eV and 0.35 eV or 0.27 eV and 0.41 eV, depending on the direction of the field with respect to the c-axis [5]. The possibility of doping lead iodide with Mn, Ni and Fe has been demonstrated but only optical characterization has been performed so far [6,7]. The influence of Zn doping on the structural and optical properties has also been studied [8].…”
Section: Introductionmentioning
confidence: 99%
“…The reason behind that the reduction in the band gaps may be of the impurity levels presented due to the accumulation of rhenium in MoSe 2 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. One of the feasible tools for studying the features of the energy bands can be caused by interlayer low energy membrane rigid phonon modes, verified by Rybak et al [23,24]. Nowadays, more sophisticated instruments are available for studying the various properties of TMDC materials with minor error corrections.…”
Section: Resultsmentioning
confidence: 99%